SIFAT ISOMORFIK PADA OPERASI TENSOR, BINTANG, CARTESIUS, DAN MODULAR DUA GRAF FUZZY - Triyani, Triyani; Guswanto, Bambang Hendriya; nurhayati, Nurhayati (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2019)
This article discusses about some isomorphic properties of  tensor, star, Cartesius, and modular product operations of two fuzzy graphs. The results of  research are the tensor product of two fuzzy graphs  is isomorphic, and if  and  are complete fuzzy graphs then , ,  and